Effect of black maca supplementation on inflammatory markers and physical fitness in male elite athletes - Lee, E.; Park, M.; Kim, B.; Kang, S. (Nutrients, 2023)
Given the current lack of studies, the primary purpose of this study was to investigate the effects of black maca supplementation intake on changes in physical strength and inflammatory markers among elite athletes. Forty-four elite athletes were recruited for the present study. They included shooting athletes, racket sports athletes, and fin swimming athletes. The intake capsules contained 2500 mg of 100% concentrated black maca extract. Participants were instructed to take one capsule twice a day for eight weeks with pure water. Changes were seen in the ATP-PC systems and aerobic energy systems, particularly in the fin swimming athletes requiring aerobic energy systems. This effect is caused by increased antioxidant activity and influenced mitochondrial biosynthesis regulatory factors due to black maca supplementation intake. These findings provide preliminary evidence that elite athletes will benefit from taking black maca to improve their inflammation levels and physical fitness.